Integrasi IoT pada Lahan Tanaman Wakaf Sebagai Media Monitoring dan Alerting pada Tumbuh Kembang Bibit Pohon Mahoni - Hernawan, Septian Rico; Novianto, Irwan; Rina, Fadmi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Environmental damage in Indonesia is concerning, with the massive loss of green spaces in recent years. Consequently, there has been a drastic decline in air quality, contributing to the rise of diseases such as stroke, heart conditions, lung diseases, and even birth defects. The implementation of environment-based waqf activities, with waqf items in the form of trees, offers a practical solution that is accessible to the public. However, this effort has not yet been widely adopted or well-facilitated. The growth of tree seedlings is influenced by several factors, such as air temperature, soil pH, humidity, and carbon particles. A method for monitoring and alerting users is needed to ensure optimal plant growth. An IoT system is integrated for the plants in the waqf areas. Sensor data will be displayed on a screen, with an alerting function that sends alarms through a speaker. Mahogany seedlings were selected for testing due to their rapid growth. Integrating IoT devices for monitoring and alerting effectively increased the height of mahogany seedlings. Based on a two-month test on 10 seedlings across two different areas, a difference of 2.4 cm per two months, or 14.4 cm per year, was observed between IoT-integrated and non-IoT areas.